Circular RNA Ttc3 regulates cardiac function after myocardial infarction by sponging miR-15b. (May 2019) - Cai, Lidong; Qi, Baozhen; Wu, Xiaoyu; Peng, Shi; Zhou, Genqing; Wei, Yong; Xu, Juan; Chen, Songwen; Liu, Shaowen
Abstract: The apoptotic death of cardiomyocytes critically contributes to cardiac remodeling after myocardial infarction (MI). Circular RNAs (circRNAs) are important regulators for a variety of biological functions. Circ-Ttc3 represents one of the top highest expressed circRNAs in the heart; however, its role in MI remains unknown. Herein, we found that circ-Ttc3 was markedly upregulated in the ischemic myocardium and the cardiomyocytes subjected to hypoxic insult. Forced expression of circ-Ttc3 in cardiomyocytes counteracted hypoxia-induced ATP depletion and apoptotic death, in sharp contrast to circ-Ttc3 knockdown. Accordingly, experiments with AAV9-cTnt-mediated knockdown of cardiac circ-Ttc3 in a rat model of MI recapitulated the in vitro findings, and showed the deterioration of cardiac dysfunction after MI. Furthermore, we identified that circ-Ttc3 sponged an endogenous miR-15b-5p to sequester and inhibit its activity, leading to the increased Arl2 expression. Conversely, knockdown of Arl2 partially abolished the beneficial effects of circ-Ttc3 overexpression on ATP production and apoptosis of cardiomyocytes. Thus, our findings revealed the cardioprotective role of circ-Ttc3 in MI. The miR-15b-Arl2 regulatory cascade underlies the protection against MI-induced cardiomyocyte apoptosis by circ-Ttc3. Highlights: Circ-Ttc3 is cardiac-enriched, and upregulated in the ischemic myocardium. Circ-Ttc3 protects cardiomyocytes from hypoxia-induced ATP depletion and apoptotic death. Reduction of circ-Ttc3 induces cardiomyocyte apoptosis and deteriorates cardiac dysfunction after MI. The circ-Ttc3-miR-15b-Arl2 regulatory cascade contributes to the circ-Ttc3-mediated cardioprotection.